Analysis of Compliance and Audit Opinion, Correlation and Causes of Failure in Detecting Non Compliance: A Study on Local Government - Habiby, Abdullah Lathif Elbaaqy; Ritonga, Irwan Taufiq (Riset Akuntansi dan Keuangan Indonesia, 2020)
This study aims to analyze the correlation between level of local government compliance with laws/regulations and audit opinions on Local Government Financial Statements (LGFS) and to identify causes of failure in detecting non-compliance, including non-compliance that contains elements of fraud, in LGFS audit. The method used is explanatory sequential mixed methods with a content analysis approach on fifty four LGFS samples and interview the auditors of the Audit Board of Republic of Indonesia (the AB). The results show that there is a correlation between level of compliance of local government and audit opinion on LGFS, but there are risk in detecting non-compliance and risk of errors in audit opinion caused by different concepts in determining fraud, unclear guidelines on compliance testing, different concept of materiality among the AB auditors, failure to update programs audit, potential threats/dangers experienced Bay auditors, and failure to reduce auditors’ negative perception on working protection. The limitation of this study is that participants only involve auditors from three representative offices originating from Java and do not conduct confirmation to the unit responsible for the preparation of audit guidelines and units that deal with legal issues. This research implied that the AB must increase effectiveness of audit quality Assurances to improve audit quality and the AB auditors should be able to apply the principle of due professional care in carrying out LGFS audit so that audit quality is maintained.